Comparative analysis of marine traffic flow in classical models. (1st September 2019) - Huang, Yamin; Yip, Tsz Leung; Wen, Yuanqiao
Abstract: Traffic flow theory has been applied to the study of marine traffic flow and underpins the phenomena being studied. This paper is intended to demonstrate the uses of classical fundamental diagrams, which are developed previously on the basis of highway traffic, by conducting empirical tests on marine traffic data. Marine traffic data are extracted from the Automatic Identification System (AIS) from Shanghai port in 2010 and 2018. Interpolation methods are used to estimate the three primary variables of fundamental diagrams, namely, flow rate, traffic density, and local speed. The relationships among these three variables are discussed and marine traffic data are further compared and contrasted with classical traffic flow models. The importance of the finding is to create consistency, predictability and uniformity of uses of fundamental diagrams on marine traffic flow. Highlights: Empirical tests of traffic flow theory applied to marine traffic. Determine the fundamental characteristics of marine traffic flow. Produce fundamental diagrams of marine traffic flow. Marine traffic flow agrees partially with the classic traffic models.